Diferentes condições de déficit hídrico na qualidade física e fisiológica de sementes de soja (Glycine max) - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The general objective of this course completion work is to evaluate the influence of different water depths on the physical quality parameters and physiology of soybean seeds after harvest. The experiment was conducted during the 2022/2023 harvest, in the experimental area of the Agricultural Engineering course, at the Federal University of Pampa, Campus Alegrete. The soybean crop was subjected to a deficient supervision regime, through a conventional sprinkler irrigation system, varying water levels in the vegetative and reproductive phases. The treatments were carried out based on the percentage of crop Evapotranspiration (ETc), being: T1: 40% of ETc in the vegetative phase and 20% reproductive, T2: 60% of ETc in the vegetative phase and 30% reproductive, T3: 80% of ETc in the vegetative phase and 40% reproductive and T4: 100% of ETc in the vegetative phase and 50% reproductive. The experimental design was randomized blocks, containing four replications for each treatment. After harvest, the seeds were sent to the university's Post-Harvest Didactic Laboratory, where quality analyzes were carried out, using the variables of electrical conductivity, emergence in the field, volumetric weight, mil weight, root length and aerial part of emergence, dry mass of roots and shoots, and initial seedling performance through seedling length variables after 7, 11 and 14 days after sowing. The results indicate that crop management under different levels of deficient supervision had a significant influence on the responses to the variations observed. Water deficit causes limitations in production, which has resulted in the use of supervision depths of less than 298 mm, resulting in a reduction in seed vigor, especially in the variables of emergence and initial plant performance. Despite this finding, the amount of water released remains beyond the total evapotranspiration required for the crop, determining predictions for the development of sustainable supervision strategies. Such strategies were not only aimed at maximizing quality, but also at adopting economically efficient practices. Keywords: Post-harvest. Sustainability. Quality. Seeds. irrigation blades.
Keywords: Engenharia agrícola; Sustentabilidade; Sementes; Colheita; Irrigação agrícola; Agricultural engineering; Sustainability; Seeds; Harvesting; Irrigation farming; CNPQ::CIENCIAS AGRARIAS